PERILAKU INTERAKSI SOSIAL MONYET HITAM DARE (MacacamauraSchinz, 1825) DI TAMAN WISATA ALAM LEJJA KABUPATEN SOPPENG - Dewi Anggita Munir; Hadijah Azis Karim; Andi Rosdayanti (Universitas Andi Djemma Palopo, 2019)
Sulawesi island is a unique island among other islands in indonesia. This research aims to find out the social interaction behaviour of Dare Black Monkey (Macaca maura) in the Lejja natural tourism park. This animal is an endemic in Sulawesi island, located in South Sulawesi Province and categorixed as an endangered species by the IUCN, therefore its existence must be protected. The method was used field observation and focal animal sampling. The object was detremined in 15 Macaca maura based on age and sexuality in a group.Social interaction behaviour was recorded, namely the behavior of playing, grooming, coitus, conflict. Based on the results that the high social behaviour frequency of playing activity was owned by the young male (72 times) and the children (56 times), as well as grooming by young male and children have the highest frequency (31 times). Frequency of coitus and agonistic behaviours was owned by adult male with 14 times and 5 times respectively.However, the longest time proportion of playing was used by children with 10.602 second (62,01%),while the total and time percentage of coitus have the lowest value (240 second or 2,11% and 300 second or 2,58% perspectively) by adult ages.Kata Kunci :, Macaca maura, social behavior, grooming, Lejja natural tourism park